FRAMING ANALYSIS OF NEWS ABOUT BENOA BAY RECLAMATION IN KOMPAS AND BALI POST DAILY NEWSPAPER EDITION JUNE 2013 – DECEMBER 2014 - Ni Wayan Primayanti (Fakultas Seni Rupa dan Desain ITB, 2016)
Centralising Southern Bali for tourism development needs some infrastructure provisions to support its activities. However, it is struggling with limited range area so a solutive way that Benoa Bay reclamation needed to be carried on remains possible. Therefore, governor's letter of permit for this reclamation has been published yet soon after the announcement, the balinese become pro and cons. Due to that fact, this issue is emerged by The national and local printed media, Kompas and Bali Post to publics. Concerning to this publication, this research aims to describe how Kompas and Bali Post report the news related to Benoa Bay reclamation. The method used is qualitative approach by using constructionist paradigm and Robert M. Entman's framing model. As the result, there are different framing report from both media including Kompas's independent news bringing up two-sides reclamation impact and Bali Post's rejection against this way to preserve Balinese valuable culture and avoid the impact to the environtment.